Two Cases of Cervical Hemorrhage with Upper Airway Obstruction: A Life-Threatening Condition - Enrico Maria Amadei; Laura Benedettini; Ottavio Piccin (Case Reports in Medicine)
Several are the causes of cervical masses and among them a spontaneous hemorrhage presents a rare and life-threatening condition. Sometimes hemorrhage develops from a previous silent neck lesion as in the case of an anaplastic thyroid carcinoma associated with bleeding. We present two cases: a 70-year-old woman suffering from enlarging cervical mass causing respiratory distress because of upper airway compression due to a spontaneous rupture of the superior thyroid artery and a 74-year-old woman who drew our attention because of a progressively worsening dyspnea due to a large medial cervical mass with rapid onset. We removed it surgically, finding out an anaplastic thyroid carcinoma that is associated with internal bleeding. We discuss our management of these rare and life-threatening conditions, recalling that the patency of upper airway should always be the prerogative in every emergency. Besides, we make a review of the recent literature.